Financing Management for Student Improvement and Development at MTsN 2 Pamekasan - Yulianto, Akhmad Haries; Abdul Aziz (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
Education financing is a strategic factor in ensuring the success of student development programs in madrasas. However, reality shows that many state madrasas, including MTsN 2 Pamekasan, still face budget limitations and strict regulations in managing BOS funds, which directly impact the effectiveness of implementing student development programs. This research examines the management of student improvement and development financing, including planning, implementation, evaluation, management strategies, challenges, and solutions. The qualitative approach is descriptive, with data collection techniques through observation, in-depth interviews, and documentation studies. Data analysis is carried out interactively through the stages of reduction, data presentation, and verification by triangulating sources. The study results show that budget planning is carried out in a structured manner, but it is still top-down; implementation follows a multi-level proposal and verification mechanism, and evaluations tend to be administrative without the participation of students and guardians. Management strategies are based on efficiency and priority scale, but funding sources are still limited to BOS and internal contributions. The main challenges include budget limitations and the rigidity of BOS techniques. The solutions implemented include savings, postponement of activities, and voluntary participation from students and guardians. This study concludes that financing management in madrassas will be more effective if it adopts a participatory, adaptive, and contextual approach to answer the real needs of students and strengthen the sustainability of educational programs.